Integração de dados baseada em ontologia - Afonso, Gustavo Ferreira (2008)
The study on data integration is not new but neither is exhausted. Its need is increasingly clear due to the search for information in a general environment with increasing availability of data proceeding from distributed and heterogeneous sources. An approach used successfully, especially to solve the problems of heterogeneity of sources, is the use of ontology, as the basis for the data integration systems. In order to employ this concept, this work describes the development of a data integration system based on ontology, DISFOQuE, which has its use as a motivation in the field of watersheds analysis.